Disorder- and Topology-Enhanced Fully Spin-Polarized Currents in Nodal Chain Spin-Gapless Semimetals - Zhou, Xiaodong; Zhang, Run-Wu; Yang, Xiuxian; Li, Xiao-Ping; Feng, Wanxiang; Mokrousov, Yuriy; Yao, Yugui (Physical Review Letters, 2022)
Recently discovered high-quality nodal chain spin-gapless semimetals MF3 (M=Pd, Mn) feature an ultraclean nodal chain in the spin up channel residing right at the Fermi level and displaying a large spin gap leading to a 100% spin polarization of transport properties. Here, we investigate both intrinsic and extrinsic contributions to anomalous and spin transport in this class of materials. The dominant intrinsic origin is found to originate entirely from the gapped nodal chains without the entanglement of any other trivial bands. The side-jump mechanism is predicted to be negligibly small, but intrinsic skew scattering enhances the intrinsic Hall and Nernst signals significantly, leading to large values of respective conductivities. Our findings open a new material platform for exploring strong anomalous and spin transport properties in magnetic topological semimetals.
CRIS-Team Scopus Importer:2023-03-27